Debunking the Monday Irrationality through the External Affection of Investors - Brahmana, Rayenda; Hooy, Chee Wooi; Ahmad, Zamri (Gadjah Mada International Journal of Business, 2016)
This study aims to reveal the mechanism of the influences of the full moon and high temperatures on investors’ Monday irrationality. In contrast to other studies, this research was built under a retroductive approach by using a time series quasi experimental study. Investors were directly assessed for their irrationality by using an adapted psychometric test on 4 occasions. The results indicate that there were indeed effects of the full moon and high temperatures on investors’ irrationality. Because the full moon and high temperatures frequently occurred on Mondays, it is most probably those two variables that were the drivers of the Monday irrationality. In the end, we concluded that the rational behaviour assumption can no longer be held. Instead of rationality, the investors were quasi rational. The utility function of Von Neumann-Morgenstern in decision making has to be replaced by the hedonic utility.